A Case Study of the Relationship between Basic Psychological Needs and General Health among Old People - Azam BAZOOBAND; Abdolvahab BAGHBANIAN; Ghazal TORKFAR (Tehran University of Medical Sciences, 2017)
A Case Study of the Relationship between Basic Psychological Needs and General Health among Old People